Establishment of an Antimicrobial Stewardship Program to Spare the Use of Oral Fluoroquinolones for Acute Uncomplicated Cystitis in Outpatients - Tomoyuki Kato; Masayuki Nagasawa; Ippei Tanaka; Yuka Seyama; Reiko Sekikawa; Shiori Yamada; Eriko Ishikawa; Kento Kitajima (MDPI AG, 2024)
The increase in fluoroquinolone (FQ)-resistant Escherichia coli (EC) is a serious global problem. In addition, much of acute uncomplicated cystitis (AUC) cases are caused by EC. FQs have been selected for the treatment of cystitis in outpatients, and there is concern about treatment failure. It is therefore necessary to select appropriate antimicrobials to spare FQs. However, there are few reported effective antimicrobial stewardship programs (ASPs) for outpatients. We aimed to establish the effective ASP for outpatients diagnosed with AUC caused by EC, to spare the use of FQs, and to explore optimal oral antimicrobials for AUC. The study subjects were outpatients treated for AUC caused by extended-spectrum β-lactamase-non-producing EC (non-ESBL-EC). Based on the antibiogram results, we recommended cefaclor (CCL) as the initial treatment for AUC, and educated clinical pharmacists who also worked together to advocate for CCL or cephalexin (CEX) prescriptions. FQ usages decreased, and cephalosporin (Ceph) prescriptions increased in all medical departments. The Ceph group (n = 114; CCL = 60, CEX = 54) in the non-FQ group had fewer treatment failures than the FQ group (n = 86) (12.3% vs. 31.4%). Cephs, including CCL and CEX, were effective treatments for AUC caused by non-ESBL-EC. Antimicrobial selection based on antibiogram results and the practice of an ASP in collaboration with clinical pharmacists were useful for optimizing antimicrobial therapy in outpatients.